2013
DOI: 10.1155/2013/420914
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Matrix Metalloproteinases in Human Breast Cancer Tissues

Abstract: Abstract. BACKGROUND:Breast cancer is the most common cancer affecting women in the world today. Matrix metalloproteinases (MMPs) are a family of endopeptidases that can degrade extracellular matrix proteins and promote cell invasion and metastasis. MMPs are differentially expressed and their expressions are often associated with a poor prognosis for patients. OBJECTIVE: The aim of this study is to investigate and compare the expression of MMPs in different grades of human breast cancer tissues with normal bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 38 publications
1
51
0
1
Order By: Relevance
“…MMP-9, together with MMP-2, activates transforming growth factor β (TGF-β) signaling to promote the invasion of the tumor, angiogenesis and metastasis. 32 The role of MMPs during the neoplastic invasion consists of the rearrangement of the extracellular matrix components in order to better accommodate cell migration. Thus, deregulation of these enzymes plays an important role in several stages of the development of breast cancer and in activities dependent on zinc binding to the catalytic site.…”
Section: Author(s) Study Design Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MMP-9, together with MMP-2, activates transforming growth factor β (TGF-β) signaling to promote the invasion of the tumor, angiogenesis and metastasis. 32 The role of MMPs during the neoplastic invasion consists of the rearrangement of the extracellular matrix components in order to better accommodate cell migration. Thus, deregulation of these enzymes plays an important role in several stages of the development of breast cancer and in activities dependent on zinc binding to the catalytic site.…”
Section: Author(s) Study Design Resultsmentioning
confidence: 99%
“…30,31 A study conducted by Benson et al 32 evaluated the expression of MMPs in different types of tissues with breast cancer and normal tissues. The results showed that MMPs are regulated differentially in tissues with breast neoplasm.…”
Section: Zinc and Metalloproteinases Of The Extracellular Matrixmentioning
confidence: 99%
“…Breast cancer cells often express high levels of MMP1, -2, -3, -9, -13, and -14 that are involved in degrading the extracellular matrix (42). Ectopic expression of MMP3 in transgenic mice was reported to develop mammary gland tumors, whereas suppression of MMP3 blocked the invasive ability of breast tumor cells (43).…”
Section: Discussionmentioning
confidence: 99%
“…3 More than 1.2 million cases are diagnosed every year, affecting 10-12% of the female population and accounting 500,000 deaths per year worldwide. 4 The incidence of breast cancer in India is 70-90 per 100,000 population and cancer prevalence is established to be around 2.5 million with over 800,000 new cases and 5,50,000 deaths occurring each year. Complete blood count is a prerequisite investigation requested from all cancer patients before surgery, use of chemotherapy and radiotherapy.…”
Section: Introductionmentioning
confidence: 99%